2020
DOI: 10.21203/rs.3.rs-33390/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV2 drives JAK1/2-dependent local and systemic complement hyper-activation

Abstract: Patients with coronavirus disease 2019 (COVID-19) present with a range of devastating acute clinical manifestations affecting the lungs, liver, kidneys and gut. The best-characterized entry receptor for the disease-causing virus SARS-CoV2, angiotensin converting enzyme (ACE) 2, is highly expressed in these tissues. However, the pathways that underlie the disease are still poorly understood. Here we show that the complement system is unexpectedly one of the intracellular pathways most highly induced by SARS-CoV… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 36 publications
1
40
0
Order By: Relevance
“…Using immunoassays in the Norwegian cohort, elevated plasma sC5b-9, C5a, C3b/iC3b/C3c, alternative pathway C3 convertase (C3bBbP), and C4d were observed in majority of COVID-19 patients in respiratory failure and were higher as compared to those that were not [ 61 ]. Similar observations were made in the lungs at the transcriptomic level, as lung biopsy samples from COVID-19 patients showed a pronounced complement signature (including C3 transcripts) following GO pathway analysis as compared to healthy controls [ 65 ]. They confirmed this observation using in vitro SARS-CoV-2-infected primary bronchial epithelial cells or a type II human pneumocyte cell line (A549) with or without ACE2 overexpression, which demonstrates a similar complement signature, which was not observed in influenza A- or respiratory syncytial virus-infected cells [ 65 ].…”
Section: Complement: Helpful Early In Covid-19 Detrimental Latesupporting
confidence: 63%
See 1 more Smart Citation
“…Using immunoassays in the Norwegian cohort, elevated plasma sC5b-9, C5a, C3b/iC3b/C3c, alternative pathway C3 convertase (C3bBbP), and C4d were observed in majority of COVID-19 patients in respiratory failure and were higher as compared to those that were not [ 61 ]. Similar observations were made in the lungs at the transcriptomic level, as lung biopsy samples from COVID-19 patients showed a pronounced complement signature (including C3 transcripts) following GO pathway analysis as compared to healthy controls [ 65 ]. They confirmed this observation using in vitro SARS-CoV-2-infected primary bronchial epithelial cells or a type II human pneumocyte cell line (A549) with or without ACE2 overexpression, which demonstrates a similar complement signature, which was not observed in influenza A- or respiratory syncytial virus-infected cells [ 65 ].…”
Section: Complement: Helpful Early In Covid-19 Detrimental Latesupporting
confidence: 63%
“…Both proteomic [ 46 , [60] , [61] , [62] , [63] , [64] ] and transcriptomic [ 62 , 65 ] studies of blood and lung samples from severe COVID-19 confirm the notion that complement activation is an immune signature characteristic of severe disease. The earliest data were observed in Chinese COVID-19 patients, as elevated serum C5a was uniquely noted in those with severe respiratory distress or hypoxia on room air as compared to those with mild symptoms or healthy controls [ 46 ].…”
Section: Complement: Helpful Early In Covid-19 Detrimental Latementioning
confidence: 92%
“…C3 is cleaved to generate activation fragments, of which C3b binds CD46 receptors on T cells. We have shown that CD4 + T lymphocytes in the lungs of patients with COVID- 19 have a CD46-activated signature 4 . CD46, engaged by T cell-generated C3b in an autocrine fashion, works co-operatively with T cell receptor stimulation to drive both Th1 differentiation and subsequent T cell shutdown 17 .…”
mentioning
confidence: 86%
“…Enrichment of the complement system in local T cells (Fig. 1c) was notable because a) we have recently identified complement as one of the most highly induced pathways in CD4 + T cells infiltrating into lung tissues 15 , b) SARS-CoV2 is a potent inducer of complement, especially complement factor 3 (C3), in lung epithelial cells 4 and c) others have previously identified the lungs of patients with COVID-19 as a complement-rich environment 16 . C3 is cleaved to generate activation fragments, of which C3b binds CD46 receptors on T cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation